2017
DOI: 10.1097/sap.0000000000000874
|View full text |Cite
|
Sign up to set email alerts
|

The Dawn of Transparency

Abstract: Background The Physician Payments Sunshine Act (PSSA) is a government initiative that requires all biomedical companies to publicly disclose payments to physicians through the Open Payments Program (OPP). The goal of this study was to utilize the OPP database and evaluate all non-research related financial transactions between plastic surgeons and biomedical companies. Methods Using the first wave of OPP data published on September 30, 2014, we studied the national distribution of industry payments made to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 34 publications
3
35
0
Order By: Relevance
“…Our data clearly show the relative importance of direct financial rewards for physicians, which is consistent with findings in other specialties, 65 , 68 , 69 and accounted for nearly two-thirds of all expenditures reported to the Open Payment repository. Most of these payments were listed as compensation for talks and presentations.…”
Section: Discussionsupporting
confidence: 89%
“…Our data clearly show the relative importance of direct financial rewards for physicians, which is consistent with findings in other specialties, 65 , 68 , 69 and accounted for nearly two-thirds of all expenditures reported to the Open Payment repository. Most of these payments were listed as compensation for talks and presentations.…”
Section: Discussionsupporting
confidence: 89%
“…The manufacturers making the most payments to ophthalmologists were also top payers in dermatology (n = 5), obstetrics and gynecology (n = 1), and plastic surgery (n = 1). 8,14,15 Similar to other specialties, ophthalmologists were reported to have received most payments in the form of meals. 2,[8][9][10][14][15][16][17][18][19][20][21] Although perhaps seemingly benign to the recipient, the acceptance of industry payments (especially meals) is not without potential consequence.…”
Section: Discussionmentioning
confidence: 88%
“…The percentage of royalties distributed as general payments to ophthalmologists (21.68%) was less than that reported to have been received by neurosurgeons (74%), orthopedic surgeons (69%), and obstetrician-gynecologists (50%) but higher than royalty payments distributed to pediatricians (15%), plastic surgeons (4%), urologists (11%), otolaryngologists (2.4%), cardiothoracic surgeons (3.8%), dermatologists (0.3%), and emergency medicine physicians (1.4%). 8,10,14,15,17,19,[24][25][26][27] Although the CMS OPD is free and publicly available, most of the population is unaware of this resource. Results from a 2018 ophthalmologic survey of 407 participants indicated that only 30 patients (7.7%) knew of the OPD and only 12 (3.1%) attempted to access the database (11 patients [2.8%] in this study were physicians).…”
Section: Discussionmentioning
confidence: 99%
“…For example, research funding has been shown to positively impact scholarly productivity [5][6][7], whereas sponsored speakerships reflect a surgeon's expertise and status as a key opinion leader [8]. However, female academic surgeons face an industry pay gap [9][10][11][12]. Within academic plastic surgery, female surgeons receive fewer industry payments and a lower monetary value per payment compared to their male counterparts [11].…”
Section: Introductionmentioning
confidence: 99%